Borealisation of Plant Communities in the Arctic Is Driven by Boreal‐Tundra Species - Mariana García Criado; Isabel C. Barrio; James D. M. Speed; Anne D. Bjorkman; Sarah C. Elmendorf; Isla H. Myers‐Smith; Rien Aerts; Juha M. Alatalo; Katlyn R. Betway‐May; Robert G. Björk; Mats P. Björkman; Daan Blok; et al. (Ecology Letters, 2025)
Following rapid climate change, tundra plant communities are experiencing extensive compositional shifts. A conservation concern is the potential encroachment of boreal species into the tundra (‘borealisation’). Tundra borealisation has been sporadically reported, but not systematically quantified. Here, we synthesised data from across 32 study areas, spanning 1137 plots and 287 vascular plant species, resurveyed between 1981 and 2023. We (i) quantified tundra borealisation as the colonisation and increase in abundance of Boreal and Boreal‐Tundra species, (ii) assessed biogeographical, climatic and local borealisation drivers and (iii) identified species contributing to borealisation and their associated traits. Half of the plots experienced borealisation, although borealisation rates were not different to random expectation. Borealisation was greater in Eurasia, closer to the treeline, at higher elevations, in warmer and wetter regions, where climate change was limited, and where initial boreal abundance was lower. Boreal coloniser species were generally short‐statured, and more often shrubs and graminoids. Boreal species colonised around three times less frequently than Boreal‐Tundra species. Hence, our findings indicate that tundra borealisation is mainly driven by the spread of already established boreal‐low Arctic tundra species. These plant community composition changes could have cascading impacts on land‐atmosphere interactions, trophic dynamics and Indigenous and local livelihoods.